Fernanda Laguna - the path of the heart - Guagnin, Nicolás; Kraus, Chris 1955-; Palmeiro, Cecilia 1975- (The Drawing Center, 2022)
"The Path of the Heart is the first English language publication devoted to the radical, pioneering work of Argentine artist Fernanda Laguna. Featuring a revealing interview with the artist by writer and critic Chris Kraus and new scholarship by Rosario Güiraldes, Cecilia Palmeiro, and Nicolás Guagnini, as well as a selection of poems by Laguna, images of over fifty artworks, and never-before-published documentary photography, this comprehensive volume explores the way Laguna's practice brings the promise of art into life"--from back cover
Impressum: Published on the occasion of the exhibition "Fernanda Laguna: The Path of the Heart" organized by Rosario Güiraldes, The Drawing Center, March 10-May 22, 2022
Keywords: Laguna, Fernanda -- 1972-; Laguna, Fernanda / 1972- / Exhibitions; Artists / Argentina / 21st century / Exhibitions; Art, Modern / 21st century / Exhibitions; Women artists / Argentina / 21st century; Exhibition catalogs; Ausstellungskatalog -- Drawing Center -- 10.03.2022-22.05.2022 -- New York, NY